THE POSSIBILITY OF THE PHILLIPED CLASSROOM MODEL IN HIGHER EDUCATION (World Bulletin of Social Sciences, 2024)
This article presents scientific recommendations for the use of flipped classroom technology in the organization of educational processes of students studying in higher education institutions.